Agent-Directed Simulation Symposium (ADS 2017) 2017
DOI: 10.22360/springsim.2017.ads.006
|View full text |Cite
|
Sign up to set email alerts
|

Aging Out of Crime: Exploring the Relationship Between Age and Crime with Agent-Based Modeling

Abstract: Criminologists have long observed a strong correlation between age and crime. The age crime relationship has withstood stringent testing since the 1920's and repeatedly demonstrated that criminal activity peaks at age seventeen and then gradually declines. These efforts have resulted in the formation of several theories; however, quantitative assessment of these theories are incomplete and fail to fully examine the role of sociological and cultural factors. In this paper, we create an agent-based model (ABM) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Yet crime trends would suggest that individuals age "in-and-out" of crime. One's propensity to commit crime peaks around 17, drops precipitously through one's early 20s, and is very low the rest of the life course (Cornelius, et al, 2017). Criminologists have found that crime trends are more closely associated with birth cohorts than other environmental variables.…”
Section: Kentmentioning
confidence: 99%
“…Yet crime trends would suggest that individuals age "in-and-out" of crime. One's propensity to commit crime peaks around 17, drops precipitously through one's early 20s, and is very low the rest of the life course (Cornelius, et al, 2017). Criminologists have found that crime trends are more closely associated with birth cohorts than other environmental variables.…”
Section: Kentmentioning
confidence: 99%